GAMBARAN PIO SWAMEDIKASI APOTEKER DALAM PENATALAKSANAAN FLU - hilda suherman (Viva Medika, 2018)
Abstract Self-medication is a human effort to treat diseases or symptoms of minor ailments such as fever, cough, flu, pain and others without a doctor's prescription. In practice, limited knowledge of drugs and their use can be a source of medication errors (medication error). This research was conducted with a cross sectional descriptive research method. Data was collected through a validated questionnaire filling technique. A total of 300 respondents involved in this study were selected by consecutive sampling method from 3 pharmacies in the city of Purwokerto which were determined proportionally according to the population of each pharmacy. Data were analyzed by Chi-square test and Fisher's test used Statistical Product and Servicer Solution (SPSS) version 17. The results showed that the patient's knowledge level was 22.6% classified as poor, 48% classified as moderate, and 29.4% classified as good. The use of self-medication is 26.3% irrational and 73.7% rational. Based on the results of the study, it was found that the patient's level of knowledge was classified as moderate with a percentage of 48%. While self-administered rationality is classified as rational with a percentage of 73.7%. Keywords: Self-medication, Pharmacy, Knowledge, Rationality of drug use